Determination of Salbutamol and Guaifenesin in Mixture Using Zero- Crossing Wavelength Measurement - Entris Sutisna; Farida Fauzia; Ida Musfiroh; Shelvy E Suherman (Indonesian Journal of Pharmaceutical Science and Technology, 2015)
A mixture of salbutamol and guaifenesin in syrup was analyzed using zero-crossing wavelength method. NaOH 0.1 N was selected as the solvent. Zero-crossing wavelength of salbutamol is 246.2 nm and guaifenesin is 270.2 nm. Results showed that the recovery of salbutamol and guaifenesin are 95.96% and 93.94%, respectively, while the coefficient of variance is 0.995% for salbutamol and 0.2087% for guaifenesin. Limit of detection of salbutamol and guaifenesin are 0.05528 ppm and 9.443 ppm, respectively, while limit of quantification are 0.18427 ppm and 31.477 ppm. We concluded that this method could be applied to determine salbutamol and guaifenesin in mixture. Keywords: Derivative spectrophotometry, guaifenesin, salbutamol, zero-crossing